RANCANG BANGUN APLIKASI E-COMMERCE DENGAN PAYMENT DAN SHIPPING GATEWAY PADA TOKO SEPUTIH.ITU - Muttaqin, Ilham; Ridwan, Mohammad; Murad, Silvia Ayunda (JURNAL TEKNIK INFORMATIKA UNIS, 2022)
Business and business activities can provide benefits for shop owners. A business activity that is run by utilizing internet technology or online commonly known as E-Commerce, at the Seputih store there are several obstacles, especially buying and selling transactions carried out by resellers. In this research, a mobile-based E-commerce application will be built using React Native and Firebase. With the E-commerce System Application that will be built, it can help shop owners in managing products and transaction data very easily. This system will use the Payment Gateway method for payment transactions, and the Shipping Gateway to check the price of shipping costs on a transaction. Both methods will be integrated with Midtrans Indonesia and RajaOngkir platforms.